Inverse problem for the diffusion operator with symmetric functions and general boundary conditions - Akhtyamov, Azamat Moukhtarovich; Sadovnichy, Victor Antonovich; Sultanaev, Yaudat Talgatovich (Eurasian Mathematical Journal, 2017)
For the inverse problem of reconstructing the nonself-adjoint diffusion operator with symmetric functions and general boundary conditions a uniqueness theorem is proved. As spectral data only one spectrum and six eigenvalues are used. Earlier this inverse problem was not considered. The inverse problem of reconstructing the self-adjoint diffusion operator with nonseparated boundary conditions was considered. To uniquely reconstruct this operator two spectra, some sequence of signs, and some complex number were used as spectral data. We show that in the symmetric case to uniquely reconstruct the self-adjoint diffusion operator one can use even less spectral data as compared with the reconstruction of a self-adjoint problem in earlier papers; more precisely, we need one spectrum and, in addition, five eigenvalues. The special cases of these general inverse problems are considered too. In these special cases less spectral data are used. Algorithms of reconstructing diffusion operator are given. Moreover, we show that results obtained in the present paper generalize the results for the inverse problem of reconstructing the diffusion operator with separated boundary conditions.